Islamic Education Learning through Google Classroom Learning Media in Relation to Learning Motivation - Al-Ghifary, Dwi Fikry; Dedih, Ujang; Sobandi, Oban (Atthulab: Islamic Religion Teaching and Learning Journal, 2022)
In the current era of technological sophistication, it encourages teachers to adjust learning media using online media. This study aims to determine students' perceptions of google classroom learning media in relation to their learning motivation. The steps in this study are, quantitative approach using correlation method, data collection tools: Obeservation, interviews, questionnaires and documentation, qualitative data using logic and for quantitative using statistical tests. The results showed that the relationship between students' perceptions of Google Classroom learning media and their learning motivation of the correlation coefficient was in the very low category of 0.01, the hypothesis was rejected meaning that there was no significant relationship, and the degree of influence of variable X on variable Y was 1%.Â Di era kecanggihan teknologi pada saat ini mendorong guru untuk menyesuaikan media pembelajaran dengan menggunakan media online. Penelitian ini bertujuan untuk mengetahui persepsi siswa terhadap media pembelajaran google classroom hubungannya dengan motivasi belajar mereka. Langkah-langkah pada penelitian ini adalah, pendekatan kuantitatif dengan menggunakan metode korelasi, alat pengumpulan data: Obeservasi, wawancara, angket dan dokumentasi, data kualitatif menggunakan pendektan logika dan untuk kuantitatif menggunakan uji statistik.Hasil penelitian menunjukkan Hubungan antara persepsi siswa terhadap media pembelajaran Google Classroom dengan motivasi belajar mereka koefisien korelasinya berada pada kategori sangat rendah yaitu 0,01, Hipotesisnya ditolak artinya tidak adanya hubungan yang siginifikan, dan derajat pengaruh variabel X terhadap variabel Y sebesar 1%.